The Genetic and Molecular Basis for Canine Models of Human Leukemia and Lymphoma - Avery, Anne C. (Frontiers in Oncology, 2020)
Emerging details of the gene expression and mutational features of canine lymphoma and leukemia demonstrate areas of similarities and differences between disease subsets in the humans and dogs. Many features of canine diffuse large B-cell lymphoma resemble the ABC form of human DLBCL, including constitutive activation of the NF-kB pathway, and almost universal presence of double expressing MYC/BCL2 lymphomas. Frequent TRAF3 mutations and absence of BCL6 expression are differences with the human disease that need further exploration. Canine peripheral T-cell lymphoma is more common in dogs than in people and behaves in a similarly aggressive manner. Common features of canine and human PTCL include activation of the PI3 kinase pathways, loss of PTEN, and the tumor suppressor CDKN2. There is insufficient data available yet to determine if canine PTCL exhibits the GATA3-TBX21 dichotomy seen in people. Common to all forms of canine lymphoproliferative disease are breed-specific predilections for subsets of disease. This is particularly striking in PTCL, with the Boxer breed being dramatically overrepresented. Breed-specific diseases provide an opportunity for uncovering genetic and environmental risk factors that can aid early diagnosis and prevention.